APLIKASI PAKAN ALAMI DAN BUATAN PADA PEMELIHARAAN LARVA UDANG VANNAME (Litopenaeus vannamei) DI HATCHERY PT. SURI TANI PEMUKA UNIT HATCHERY NEGARA, BALI - Aonullah, Asep Akmal; Manida, Aliyati (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
This study aims to determine the application of live and artificial feed in the rearing of vanname shrimp larvae (Litopenaeus vannamei). The work consists of preparation of rearing media, nauplii stocking, feed management and monitoring of larval rearing. A total of 2,000,000 nauplii were used and reared in concrete tanks with a water volume capacity of 14 tons equipped with a filtration system and water changes carried out by flowtrough and circulation. The feed used consisted of livel feed including Chaetoceros muelleri, Thalassiosira sp and Artemia sp. and also artificial feed (commercial feed). The results showed that the application of live and artificial feed during larval rearing was positively correlated with larval stadia development and larval survival rate. Larval development in each stadia, including zoea, mysis and post larvae, showed normal development. The total larval population at each stadia decreased with a final mortality value of 40%. Nevertheless, the survival rate until the end of the PL-10 rearing period was observed to be 60% and this condition was in optimal condition